THE INFLUENCE OF PERSONAL HYGIENE EDUCATION THROUGH VIDEO MEDIA ON KNOWLEDGE, ATTITUDES AND PERCEPTIONS OF PERSONAL HYGIENE GENETALIA IN YOUNG WOMEN - Ernawati, Ernawati; Maryati, Ida; Murtiningsih, Murtiningsih (Jurnal Kesehatan, 2025)
Young women in Islamic boarding schools don’t receive education about personal hygiene in genetics and don’t have sufficient access to sources of information. Within the scope of Islamic boarding schools, no counseling or programs are ever carried out, only how to maintain personal hygiene as a whole. The phenomenon found in young women in Islamic boarding schools is that there is still very little knowledge about personal genetic hygiene. The results of a preliminary study conducted on the board of supervisors of female Islamic boarding schools predominantly do not yet know about good genetic personal hygiene. The aim of the research is to determine the difference between personal hygiene education through video and leaflet media on knowledge, attitudes and perceptions of personal hygiene for young women in Islamic boarding schools, Kec. Kahu District Bone. The type of research used was a quasi-experiment with a Pretest Posttest Two Group Design. The sample in this study was the total population where the sample at the Darul Abrar Islamic boarding school (intervention group) was 40 female students and the Al Balaq Islamic boarding school (control group) was 40 female students. Sample selection was total sampling. The data collection technique used was to divide into 2 groups where 40 people were given video media and 40 people were given leaflet media. The research results showed that video media had a significant effect compared to leaflet media on personal hygiene of genetics because the video presented by the researcher was very clear and the respondents listened and analyzed what they saw from the video presented during the research. This research has important implications in nursing management, especially regarding personal genital hygiene because it requires cooperation from related parties in socializing to teenagers how important it is to carry out personal genital hygiene.